Role of the repeat expansion size in predicting age of onset and severity in RFC1 disease - Currò Riccardo; Dominik Natalia; Facchini Stefano; Vegezzi Elisa; Sullivan Roisin; Galassi Deforie Valentina; Fernández-Eulate Gorka; Traschütz Andreas; Rossi Salvatore; Garibaldi Matteo; Kwarciany Mariusz; Taroni Franco; et al. (Oxford University Press, 2026)
RFC1 disease, caused by biallelic repeat expansion in RFC1, is clinically heterogeneous in terms of age of onset, disease progression and phenotype. We investigated the role of the repeat size in influencing clinical variables in RFC1 disease. We also assessed the presence and role of meiotic and somatic instability of the repeat. In this study, we identified 553 patients carrying biallelic RFC1 expansions and measured the repeat expansion size in 392 cases. Pearson's coefficient was calculated to assess the correlation between the repeat size and age at disease onset. A Cox model with robust cluster standard errors was adopted to describe the effect of repeat size on age at disease onset, on age at onset of each individual symptoms, and on disease progression. A quasi-Poisson regression model was used to analyse the relationship between phenotype and repeat size. We performed multivariate linear regression to assess the association of the repeat size with the degree of cerebellar atrophy. Meiotic stability was assessed by Southern blotting on first-degree relatives of 27 probands. Finally, somatic instability was investigated by optical genome mapping on cerebellar and frontal cortex and unaffected peripheral tissue from four post-mortem cases. A larger repeat size of both smaller and larger allele was associated with an earlier age at neurological onset [smaller allele hazard ratio (HR) = 2.06, P < 0.001; larger allele HR = 1.53, P < 0.001] and with a higher hazard of developing disabling symptoms, such as dysarthria or dysphagia (smaller allele HR = 3.40, P < 0.001; larger allele HR = 1.71, P = 0.002) or loss of independent walking (smaller allele HR = 2.78, P < 0.001; larger allele HR = 1.60; P < 0.001) earlier in disease course. Patients with more complex phenotypes carried larger expansions [smaller allele: complex neuropathy rate ratio (RR) = 1.30, P = 0.003; cerebellar ataxia, neuropathy and vestibular areflexia syndrome (CANVAS) RR = 1.34, P < 0.001; larger allele: complex neuropathy RR = 1.33, P = 0.008; CANVAS RR = 1.31, P = 0.009]. Furthermore, larger repeat expansions in the smaller allele were associated with more pronounced cerebellar vermis atrophy (lobules I-V β = -1.06, P < 0.001; lobules VI-VII β = -0.34, P = 0.005). The repeat did not show significant instability during vertical transmission and across different tissues and brain regions. RFC1 repeat size, particularly of the smaller allele, is one of the determinants of variability in RFC1 disease and represents a key prognostic factor to predict disease onset, phenotype and severity. Assessing the repeat size is warranted as part of the diagnostic test for RFC1 expansion.